PENGUKURAN TINGKAT KEBISINGAN PADA KAPAL COASTER - Sasono, Eko Julianto (Department of Naval Architecture - Diponegoro University, 2007)
The noise on the ship is a fitness factor. When it is over, can effect the healthy and concentration of crews, finally it can effect safety of ships. The rules of noise level for commercial ship is inserted in â€Code on noise levels on board shipsâ€ of IMO. The noise level evaluate of Coaster ship have done when the main machine speed is 85 % MCR. The evaluate used Noise Onsoku of equipment. The navigation when it was evaluated was sea trial. As a result, the noise level of Coaster ship is still get the specification of IMO codes.